Dermatitis artefacta: Three case reports - Walia N (Wolters Kluwer Medknow Publications, 2006)
Three cases of dermatitis artefacta are reported for their varied presentation, diagnostic indicators and complex management. A 21-year-old soldier had multiple painful erosions on dorsum of both forearms of three weeks duration normal with inbetween skin. By occlusive bandaging dressing lesions healed without recurrence. A 28-year-old mechanic had recurrent blisters with non healing wounds on the right knee without surrounding inflammation. Histopathology was nonspecific. A young soldier had multiple asymphomatic nodular lesion in linear distribution on right forearm of two years induration. Biopsy showed features of scar. Psychiatric evaluation and follow-up was essential in all cases.